2016
DOI: 10.1172/jci84871
|View full text |Cite
|
Sign up to set email alerts
|

Opposing actions of angiopoietin-2 on Tie2 signaling and FOXO1 activation

Abstract: tributed to the design of experiments, data analysis, and interpretation of results. PB provided transgenic mice. DMM contributed to the design of experiments, data analysis, interpretation of results, and writing of the manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
193
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 186 publications
(212 citation statements)
references
References 77 publications
(166 reference statements)
11
193
0
Order By: Relevance
“…(61). Furthermore, the agonist activity of recombinant ANG2 can be increased by tetramer formation or the chimeric domains used to increase ANG2 solubility and stability (70,71).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(61). Furthermore, the agonist activity of recombinant ANG2 can be increased by tetramer formation or the chimeric domains used to increase ANG2 solubility and stability (70,71).…”
Section: Methodsmentioning
confidence: 99%
“…(61). Furthermore, the agonist activity of recombinant ANG2 can be increased by tetramer formation or the chimeric domains used to increase ANG2 solubility and stability (70,71).LPS triggers ANG2 release and decreases ANG1-Tie2/Tie1 signaling. Recombinant ANG1, inhibition of ANG2 or increasing Tie2 activity by therapeutic antibodies or a small-molecule phosphatase inhibitor have vascular protective effects in acute inflammation and in sepsis (32,33,34,62,72,73), consistent with an agonist action of ANG1 and antagonistic action of ANG2.…”
mentioning
confidence: 99%
“…Both in cultured ECs and in conditional Tie1-knockout mice, endothelial expression of Tie1 was required for the agonist effects of both ANG1 and autocrine ANG2 on Tie2 activation and vascular remodeling. Furthermore, in support of the Kim et al study (36), Korhonen and colleagues also have shown that endotoxemia-induced cleavage of the Tie1 ectodomain reduces ANG2-mediated Tie2 phosphorylation, decreases downstream AKT activation, and increases nuclear localization of FOXO1. Based on these findings, Korhonen and colleagues propose a model in which Tie1 interacts with Tie2 at baseline to promote angiopoietin signaling, but is cleaved in the setting of inflammation, resulting in loss of ANG2 agonist activity and thereby promoting adverse vascular remodeling and leakiness.…”
Section: Remaining Questions and Implications For Therapymentioning
confidence: 65%
“…Using inhibitory antibodies targeting ANG2 and Tie2 along with powerful mouse models, Kim et al demonstrated that ANG2 antagonism of Tie2 promotes loss of vascular integrity during infection with Mycoplasma pulmonis (36). Moreover, compromised vascular integrity was further exacerbated by antibody-mediated inhibition of Tie2 activation.…”
Section: The Effect Of Inflammationmentioning
confidence: 99%
See 1 more Smart Citation